Investigação experimental da relação entre temperatura e impedância elétrica de biomaterial - fígado bovino e modelagem de ablação por radiofrequência para tratar tumor hepático - (:unkn) unknown (Universidade Federal do Pampa, 2016)
Cancer is a leading cause of death worldwide, killing more than 8 million of people a year, making the cancer one of the worst of our generation and affecting thousands of families around the world. In developing countries these numbers become worse, since disease detection is later and only conventional treatments are used, which are often ineffective and cause many collateral effects. Radiofrequency ablation (RFA) is a treatment against cancer that applies thermal energy generated by passing electric current from an electrode inserted in the tumor to kill cancer cells. This procedure is minimally invasive and not presents significant collateral effects, so that the patient can go home one day after the treatment. Aiming to expand and facilitate the use of RFA, mathematical modeling software (RAFEM) that uses finite element method to simulate tumor ablation was developed. With the aid of this software doctors will be able to optimize the process parameters, such as voltage, power and application time. RFA experiments were performed to find out which parameters influence the process, such as the maximum temperature reached by the electrode during the process. It was found that the temperature at the electrode tip exceeds 100°C, causing tissue necrosis in the tip region. The relationship of the electrode surface temperature vs time was used as an input parameter of the software to perform the simulations. The results were validated by comparison with experimental data obtained by Mulier et al. (2015). The RAFEM software was proved to be effective in the simulation of the effects caused by the RFA process. This makes it to be a potential tool to assist doctors and patients in the treatment against cancer.
Keywords: Engenharia; Radiofrequência; Método dos elementos finitos; Tumor hepático; Engineering; Radiofrequency; Finite element method; Hepatic tumor; CNPQ::ENGENHARIAS